2016
DOI: 10.1111/tbed.12492
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model to Rank Shellfish Farming Areas Based on the Risk of Disease Introduction and Spread

Abstract: Summary The European Union Council Directive 2006/88/EC requires that risk‐based surveillance (RBS) for listed aquatic animal diseases is applied to all aquaculture production businesses. The principle behind this is the efficient use of resources directed towards high‐risk farm categories, animal types and geographic areas. To achieve this requirement, fish and shellfish farms must be ranked according to their risk of disease introduction and spread. We present a method to risk rank shellfish farming areas ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This study showed that a questionnaire does not suffice to gather farm data of a sufficient quality for performing a risk-based surveillance of aquaculture facilities. However, depending on the resources available, it might not be possible for the authorities to visit every single farm on a regular basis for the collection of data necessary for a risk analysis (Thrush et al 2016). Moreover, the cost-benefit ratio of collecting field data versus relying solely on questionnaire data needs to be considered.…”
Section: Data Collection For Risk-based Surveillance Of Aquaculture Fmentioning
confidence: 99%
“…This study showed that a questionnaire does not suffice to gather farm data of a sufficient quality for performing a risk-based surveillance of aquaculture facilities. However, depending on the resources available, it might not be possible for the authorities to visit every single farm on a regular basis for the collection of data necessary for a risk analysis (Thrush et al 2016). Moreover, the cost-benefit ratio of collecting field data versus relying solely on questionnaire data needs to be considered.…”
Section: Data Collection For Risk-based Surveillance Of Aquaculture Fmentioning
confidence: 99%
“…Several studies have assessed the impact of global changes, in cluding those related to climate, on the growth and biogeo graphy of cultivated bivalves (Guyondet et al 2015, Filgueira et al 2016, Thomas et al 2016, Thomas & Bacher 2018, Steeves et al 2018). Modelling tools have also been developed to assess disease propagation amongst individuals and be tween farms and to potentially help the producers facing these phenomena (Thrush et al 2017, Gang nery et al 2019, Lupo et al 2019, 2020. Due to their complexity, few models allow the combination of a large number of changing scenarios to help with decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the items not displayed in other 1, other 2 and other 3 are as follows. (Allepuz et al, 2018;Van Limbergen et al, 2018 (Thrush et al, 2017;Allepuz et al, 2018…”
mentioning
confidence: 99%